Assessing the eco-efficiency of industrial parks recycling transformation: Evidence from data envelopment analysis (DEA) and fuzzy set qualitative comparative analysis (fsQCA) - Lei, Zhen; Wei, Junrong (Frontiers in Environmental Science, 2023)
Industrial parks that used to be one of the typical vehicles for regional economic development have witnessed the decay of traditional linear growth models. For instance, especially in emerging economies such as China, industrial park recycling transformation (IPRT) is at its high time to be fully involved. However, more efforts are needed to verify the performance evaluation and promotion paths. To fill the void, using the sample of 21 demonstration pilot industrial parks in Jiangsu province, China, from 2012 to 2015, the IPRT eco-efficiency evaluations were conducted using the super-efficiency data envelopment analysis model. Then the authors analyzed the paths to promote IPRT via fuzzy set qualitative comparative analysis. The results suggest that IPRT has progressed notably while the performance varies. Building on the Technology-Organization-Environment framework, the authors conducted a configurational analysis to enhance IPRT performance. The findings indicate that high eco-efficiency results from multiple factors and interactions with environmental supervision intensity playing a pivotal role. The result also shows that the local economic development level and parks' technological capacity are substitutable. Parks in regions with a modest economy undergo an environment-technology-oriented transformation; external factors mainly drive IPRT in areas with a developed economy. As such, the efforts enlighten parks to adopt proper strategy profiles and offer policy options for governments.